Evaluasi Sistem Antrian Pada Loket Pendaftaran Puskesmas Unter Iwes Kecamatan Sumbawa - Hermanto, Koko; Sakina, Cici Putri; Utami, Silvia Firda; Harizahayu, Harizahayu (UJMC (Unisda Journal of Mathematics and Computer Science), 2024)
The best service includes providing fast service so that customers can arrive quickly. The service here can be in the form of improving the queuing system. Queues can occur if the need for a service exceeds the available demand. One service sector with a queuing system is the Community Health Center. The Community Health Center is a functional implementing unit that is a health development center for fostering community participation in the health sector. So, research was carried out to evaluate the queuing system at the Unter Iwes Health Center registration counter in Sumbawa District to optimize queuing services. The study results show that the queuing system currently used at the registration counter at the Unter Iwes Health Center, Sumbawa sub-district, namely Single Channel-Single Phase, is still optimal, as indicated by a steady state value of less than one. On Monday, it was found that the average queue in the system (????s) was one person, the average queue in the queue (????q) was one person, while the probability that the number of patients in the queue would not occur (????o) was 0%. The average waiting time in the system (????s) is 0.24 minutes, while the average waiting time in the queue (????q) is 0.15 minutes, the server busy level (K) is 64%, and the server unemployment level (W) is 36%.